2020
DOI: 10.1111/tpj.14884
|View full text |Cite
|
Sign up to set email alerts
|

ERF4 affects fruit firmness through TPL4 by reducing ethylene production

Abstract: Summary The firmness of fleshy fruit crops has a significant effect on their quality, consumer preference, shelf life and transportability. In a combined quantitative trait locus and genome‐wide association studies study of apple fruit texture, we identified a mutation (C‐G) in the ethylene response factor‐associated amphiphilic repression (EAR) motif in the coding region of the apple ETHYLENE RESPONSE FACTOR4 (ERF4) gene. Chromatin immunoprecipitation sequencing showed that ERF4 binds to the promoter of ERF3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 56 publications
2
49
0
Order By: Relevance
“…Low temperatures clearly induced the expression of both genes, with peak MdACS1 and MdACO1 transcription levels detected at 8 h (about 10‐fold) and 12 h (about 6‐fold), respectively, followed by a gradual decrease (Figure 2b). The following six TFs have been identified as important regulators associated with the ethylene synthesis: MdEIL1 (An et al ., 2018a), MdERF1 (Wang et al ., 2007), MdERF1B (Zhang et al ., 2018), MdERF2 (Wang et al ., 2007), MdERF3 (Li et al ., 2016), and MdERF4 (Hu et al ., 2020). As shown in Figure 2(b), cold stress treatment upregulated the transcription of MdEIL1 , MdERF1B , MdERF2 , and MdERF3 to varying degrees.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low temperatures clearly induced the expression of both genes, with peak MdACS1 and MdACO1 transcription levels detected at 8 h (about 10‐fold) and 12 h (about 6‐fold), respectively, followed by a gradual decrease (Figure 2b). The following six TFs have been identified as important regulators associated with the ethylene synthesis: MdEIL1 (An et al ., 2018a), MdERF1 (Wang et al ., 2007), MdERF1B (Zhang et al ., 2018), MdERF2 (Wang et al ., 2007), MdERF3 (Li et al ., 2016), and MdERF4 (Hu et al ., 2020). As shown in Figure 2(b), cold stress treatment upregulated the transcription of MdEIL1 , MdERF1B , MdERF2 , and MdERF3 to varying degrees.…”
Section: Resultsmentioning
confidence: 99%
“…Because several ERF TFs can link ethylene production with stress responses (An et al ., 2018b; Hu et al ., 2020; Li et al ., 2016; Zhang and Huang, 2010), we further verified whether MdERF1B regulated ethylene production in apple. The expression levels of MdACO1 and MdERF3 were obviously higher in the MdERF1B‐OX calli than in the WT calli (Figure 7a).…”
Section: Resultsmentioning
confidence: 99%
“…The existence of ERF with negative regulation might balance the speed of fruit ripening, which prevents the fruit from ripening too quickly, and is helpful for attracting animals to disperse seeds. In addition, MdERF4 binds to the MdERF3 promoter and represses its expression [29]. A mutation (C-G) was identified in the ethylene response factor-associated amphiphilic repression (EAR) motif of the MdERF4 coding region.…”
Section: Ethylenementioning
confidence: 99%
“…A mutation (C-G) was identified in the ethylene response factor-associated amphiphilic repression (EAR) motif of the MdERF4 coding region. The EAR mutation of MdERF4 leads to reduced inhibition of MdERF3 expression, which in turn promotes ethylene biosynthesis [29].…”
Section: Ethylenementioning
confidence: 99%
“…This results revealed that all 13 genes displayed the same trend, and the Pearson correlation coefficient between RNA-seq and qRT-PCR data was 0.92 (P < 0.0001), indicating that the RNA-seq was reliable (Supplementary Figure 4). The TPL/TPR family of co-repressors functions as a central regulatory hub regulating all nine phytohormone pathways and controlling plant development, including meristem maintenance, fruit ripening, and anthocyanin accumulation (Gallavotti et al, 2010;Fukazawa et al, 2014;Hao et al, 2014;Qu et al, 2019;Hu et al, 2020). As TPL proteins lack DNA-binding activity, they are incorporated into transcription complexes by interacting with transcription factors to repress gene expression in various processes (Causier et al, 2012(Causier et al, , 2014.…”
Section: Validation Of Rna-seq Data By Qrt-pcrmentioning
confidence: 99%